Measuring sustainability efficiency at farm level: a data envelopment analysis approach. (14th May 2019) - Ait Sidhoum, Amer; Serra, Teresa; Latruffe, Laure
Abstract: Sound implementation of sustainability practices requires appropriate tools to measure farms' successes in achieving policy goals. This paper models farms' stochastic production technology as the interaction of three main types of sub-technologies that govern, respectively, the production of agricultural commodities, environmental (nitrogen and pesticide) pollution and social outputs of agricultural activities. The model is empirically implemented through a Data Envelopment Analysis (DEA) model accounting for production risk through a state-contingent approach. The application for Catalan arable crop farms shows that, on average, farms display high technical and social performance and relatively poor environmental performance.